Sex-specific tonic 2-arachidonoylglycerol signaling at inhibitory inputs onto dopamine neurons of Lister Hooded rats - Melis, Miriam; De Felice, Marta; Lecca, Salvatore; Fattore, Liana; Pistis, Marco (Frontiers in Integrative Neuroscience, 2013)
Addiction as a psychiatric disorder involves interaction of inherited predispositions and environmental factors. Similarly to humans, laboratory animals self-administer addictive drugs, whose appetitive properties result from activation and suppression of brain reward and aversive pathways, respectively. The ventral tegmental area (VTA) where dopamine (DA) cells are located is a key component of brain reward circuitry, whereas the rostromedial tegmental nucleus (RMTg) critically regulates aversive behaviors. Reduced responses to either aversive intrinsic components of addictive drugs or to negative consequences of compulsive drug taking might contribute to vulnerability to addiction. In this regard, female Lister Hooded (LH) rats are more vulnerable than male counterparts to cannabinoid self-administration. We, therefore, took advantage of sex differences displayed by LH rats, and studied VTA DA neuronal properties to unveil functional differences. Electrophysiological properties of DA cells were examined performing either single cell extracellular recordings in anesthetized rats or whole-cell patch-clamp recordings in slices. In vivo, DA cell spontaneous activity was similar, though sex differences were observed in RMTg-induced inhibition of DA neurons. In vitro, DA cells showed similar intrinsic and synaptic properties. However, females displayed larger depolarization-induced suppression of inhibition (DSI) than males. DSI, an endocannabinoid-mediated form of short term plasticity, was mediated by 2-arachidonoylglycerol (2-AG) activating type 1-cannabinoid (CB1) receptors. We found that sex-dependent differences in DSI magnitude were not ascribed to CB1 number and/or function, but rather to a tonic 2-AG signalling. We suggest that sex specific tonic 2-AG signaling might contribute to regulate responses to aversive intrinsic properties to cannabinoids, thus resulting in faster acquisition/initiation of cannabinoid taking and, eventually, in progression to addiction